The effect of spiritual emotional freedom technique (seft) therapy on sleep quality in elderly in tebes lues village, bies district, Central Aceh district year 2022 - Rosmani Sinaga (Institute of Computer Science (IOCS), 2022)
Elderly is an age where individuals will experience various declines in their abilities. In general, this aging process can cause various problems, both physically, biologically, mentally, socially and economically. There are two types of management that can be done, namely pharmacological and non-pharmacological management, one of which is Spiritual Emotional Freedom Technique (SEFT) therapy. This study aims to identify the effect of Spiritual Emotional Freedom Technique (SEFT) therapy on sleep quality in the elderly in Tebes Lues Village, Bies District, Central Aceh Regency in 2022. The method used in this study is a quasi-experimental or quasi- experimental. The type of design in this study is in the form of a non-equivalent design (pretest and posttest) control group design. The pre-test sleep quality in the intervention group was mostly in the moderate category of 9 (52.9%), and the post-test sleep quality was mostly in the mild category of 10 (58.5%). The pre-test sleep quality in the control group was mostly in the heavy category 10 (58.5%), and the post-test sleep quality was mostly in the heavy category 11 (64.7%). There is a significant difference in sleep quality before and after being given the Spiritual Emotional Freedom Technique (SEFT) in the intervention group with a p-value of 0.000